Answer: Cost per pair of jeans = $ 20
Cost per pair of shorts = $12
Cost per shirt = $8
Step-by-step explanation:
Let x= cost per pair of jeans
y = Cost per pair of shorts
z= cost per shirt.
For you, total cost = x+4y+2z= 84
For your friend, total cost = 2x+y+3z=76
For cousin, total cost = x+2y+z= 52
Required system:
[tex]x+4y+2z=84\ (i)\\ 2x+y+3z=76\ (ii)\\ x+2y+z=52\ (iii)[/tex]
from (i), [tex]x=84-4y-2z[/tex] (*)
put this in (ii) and (iii) we get
[tex]2\left(84-4y-2z\right)+y+3z=76\\\Rightarrow\ -7y-z+168=76\ (iv)\\\\ 84-4y-2z+2y+z=52\\\Rightarrow\ -2y-z+84=52 \ (v)[/tex]
from (iv), [tex]y=-\frac{z-92}{7}\ (vi)[/tex]
[tex]\mathrm{Subsititute\:}y=-\frac{z-92}{7}\ \text{in}\ (v)[/tex]
[tex]-2\left(-\frac{z-92}{7}\right)-z+84=52\\\\\Rightarrow\ -2\left(-\frac{z-92}{7}\right)-z=-32\\\\\Rightarrow\ -\frac{5z}{7}-\frac{184}{7}=-32\\\\\Rightarrow\ -5z-184=-224\\\\\Rightarrow\ -5z=-40\\\\\Rightarrow\ z=8[/tex]
[tex]\mathrm{Subsititute\:}z=8\text{ in (vi)}[/tex]
[tex]y=-\frac{8-92}{7}\\\\\Rightarrow \ y=12[/tex]
[tex]\mathrm{Subsititute\:}z=8,\:y=12\text{ in (*)}[/tex]
[tex]x=84-4\cdot \:12-2\cdot \:8\\\\\Rightarrow\ x= 20[/tex]
Hence, x= 20, y= 12 , z=8
So, Cost per pair of jeans = $ 20
Cost per pair of shorts = $12
Cost per shirt = $8